2006
DOI: 10.1110/ps.051781406
|View full text |Cite
|
Sign up to set email alerts
|

Conformational changes of the glucocorticoid receptor ligand binding domain induced by ligand and cofactor binding, and the location of cofactor binding sites determined by hydrogen/deuterium exchange mass spectrometry

Abstract: HXMS (hydrogen/deuterium exchange mass spectrometry) of the glucocorticoid receptor ligandbinding domain (GR LBD) complexed with the agonist dexamethasone and the antagonist RU-486 is described. Variations in the rates of exchange were observed in regions consistent with the published crystal structures of GR LBD complexed with RU-486 when compared with the GR dexamethasone complex. We also report the HXMS results for agonist-bound GR LBD with the coactivator transcriptional intermediary factor 2 (TIF2) and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 24 publications
5
40
0
1
Order By: Relevance
“…These inverted responses were then shown to depend upon the joint actions of the N-and C-terminal domains of each receptor (Song et al, 2001). These results are consistent with the demonstration that corepressors interact with N-terminal regions of both GRs and PRs Wang et al, 2007) in addition to the initially defined requirements of the C-terminal sequences of nuclear (Zamir et al, 1996) and steroid receptors (Cheng et al, 2002;Wang et al, 2004a;Frego and Davidson, 2006;Wu et al, 2006;Kroe et al, 2007;Wang et al, 2007).…”
Section: Introductionsupporting
confidence: 89%
“…These inverted responses were then shown to depend upon the joint actions of the N-and C-terminal domains of each receptor (Song et al, 2001). These results are consistent with the demonstration that corepressors interact with N-terminal regions of both GRs and PRs Wang et al, 2007) in addition to the initially defined requirements of the C-terminal sequences of nuclear (Zamir et al, 1996) and steroid receptors (Cheng et al, 2002;Wang et al, 2004a;Frego and Davidson, 2006;Wu et al, 2006;Kroe et al, 2007;Wang et al, 2007).…”
Section: Introductionsupporting
confidence: 89%
“…This profile is similar, but not identical, to the profile of a known antagonist, RU486. Interactions with corepressors have been documented for GR previously in response to antagonists (32,33). These results suggest that LGD5552-bound GR can adopt a conformation that also accommodates larger corepressor peptides (34).…”
Section: Discussionmentioning
confidence: 59%
“…To facilitate this ligand binding study, unlabeled dex remaining from the protein preparation was removed from solution through dialysis or desalt- ing. Previous studies (58,60,64) have shown that recombinantly expressed GR LBD can readily exchange ligand under non-denaturing conditions, in sharp contrast with the androgen receptor, 4 suggesting ligand binding pocket accessibility may be a feature of GR. Fig.…”
Section: Gr Ligandmentioning
confidence: 98%
“…Biochemical interrogation of GR LBD and its various interaction partners has long been hindered by difficulty in obtaining stable, functional receptors for in vitro studies. The majority of published work using recombinantly expressed GR LBD, including this study, has been aided by incorporation of solubility-enhancing mutations discovered by yeast screens of GR activity (58,59,64), 3 and GR containing the mutations F602S and C638D will be referred to henceforth as GR SD .…”
Section: Gr Ligandmentioning
confidence: 99%